Application of precision care model based on symptom management theory for patients after intersphincteric resection - YIN Yan; ZHANG Jie; HE Wenbin; DUAN Jing; LI Sisi; JIANG Congqing; XIE Xiaoyu; HU Xiaona; XIE Huixuan; LUO Man; SUN Wen (Yixue xinzhi zazhi)
Objective To explore the effects of precision care model for patients after intersphincteric resection based on symptom management theory.Methods Patients with intersphincteric resection in the colorectal and anal surgery department of Zhongnan Hospital of Wuhan University from June 2023 to March 2024 were prospectively selected by non-randomized concurrent controlled trail, and they were divided into the control group and the trial group according to the order of admission time. The control group received routine care, and the trial group received precision care model based on symptom management theory on the basis of the intervention in the control group. The anorectal function, anastomotic incidence and quality of life were compared between the two groups after intersphincteric resection.Results A total of 111 patients were enrolled in the study, with 56 in the trial group and 55 in the control group. The excellent rate of anorectal function in the trial group was significantly higher than that in the control group after surgery (69.64% vs. 34.55%, P0.05).Conclusion The precise care model based on symptom management theory can effectively restore the anorectal function of patients and improve the quality of life of patients after intersphincteric resection.